Analysis of Expansive Fiscal Policy and Grants on International Trade in Indonesia - Fuddin Muhammad khoirul; Della Nurisa Agustin (Universitas Hayam Wuruk Perbanas, 2025)
This study aims to determine the long-term and short-term effects of Government Expenditure, External Debt, and Grants variables on the Current Account Balance. This model uses the Vector Error Correction Model (VECM) model to achieve a longterm and short-term balance. This study uses secondary data from world banks during the period 1983-2022 in Indonesia. This study proves that in the long run, Government Expenditure and Grants have a significant effect on the Current Account Balance. However, External Debt did not have a significant effect on the Current Account Balance. On the other hand, in the short term, Government Expenditure, External Debt, and Grants did not show a significant influence on the Current Account Balance. This study emphasizes the importance of the role of the Current Account Balance as the main pillar in assessing the level of economic progress in Indonesia. Expansive fiscal policy through increased government expenditure can strengthen the economy, especially when there is a surplus in the Current Account Balance. In addition, external debt can be used to cover the current account deficit, which ultimately has the potential to create a surplus. The influence of grants also has the potential to expand the reach of international trade, which has a positive impact on the Current Account Balance.